siMS score- method for quantification of metabolic syndrome, confirms co-founding factors of metabolic syndrome - Dimitrijevic-Sreckovic, V.; Petrovic, H.; Dobrosavljevic, D.; Colak, E.; Ivanovic, N.; Gostiljac, D.; Ilic, S.; Nikolic, D.; Gacic, J.; Soldatovic, I. (Frontiers in Genetics, 2023)
Background:Adipose tissue is a dynamic endocrine organ, a highly active metabolic tissue, and an important source of cytokines. Inflammatory factors play an important role in visceral obesity associated with insulin resistance (IR), metabolic syndrome (MS), hypertension, non-alcoholic fat liver disease (NAFLD), diabetes mellitus type 2 (DM2), endothelial dysfunction (ED) and atherosclerosis. Objectives:To examine corelation of siMS score, as a quantification method for MS, with IR, glucoregulation parameters, as with other co-founding factors of MS, inflammation and thrombosis factors, microalbuminuria, uric acid, fatty liver index (FLI) and homocysteine. Methods:The study included 451 obese individuals with Pre–MS and MS (age 16-75, body mass index (BMI)>25kg/m2) classified into two groups: I-age 10-30 (167 patients); II-age 31-75 (284 patients). IDF classification was applied for diagnosing MS. Patients with less than three criteria indicated below were considered pre-MS. siMS risk score by Soldatovic I et al. 2016 was used. Results:siMS score increased with age: I-3.03±0.87,II-3.27±0.90. siMS score correlated with associated factors of MS: hyperinsulinemia and IR, ALT, gama-GT, FLI, uric acid in both groups and CRP (p<0.01) in group I. Correlations in II group: siMS score with PAI-1 (p=0.01), microalbuminuria (p=0.006), homocysteine (p=0.076). Conclusion:Correlation of siMS score with HOMA-IR confirmed that hyperinsulinism and IR are in the basis of MS. Correlation of siMS score with parameters of NAFLD, CRP, PAI-1, uric acid, microalbuminuria and homocysteine indicates that they are significant co-founding factors of MS. Correlation of siMS score with PAI-1, microalbuminuria, homocysteine, indicates higher risk for progression of endothelial dysfunction and atherosclerosis with age